Shifted Retrofit Thermodynamic Diagram: A Modified Tool for Retrofitting Heat Exchanger Networks - J.Y. Yong; P.S. Varbanov; J.J. Klemeš (Chemical Engineering Transactions, 2014)
Chemical industries are constantly looking for ways to improve the plants’ energy efficiencies due to increasing energy price. One of the ways is to perform retrofit on heat exchanger networks. Over the decades, much research has been performed in this area and can be generally classified into insight-based methods and optimisation-based methods. In this paper, Shifted Retrofit Thermodynamic Diagram (SRTD) is introduced, which is a modification from Retrofit Thermodynamic Diagram (RTD) is found in literature. SRTD has the features of RTD and incorporates thermodynamic feasibility representation as well as minimum allowed temperature difference. This paper also includes an illustrative case study.